Improved calibration for non destructive determination of manganese in metallurgical tap smelting slag using a high energy medical accelerator - Togia, N.; Vasilopoulou, T.; Filippaki, E.; Savva, M. I.; Georgolopoulou, P.; Mertzimekis, T. J.; Basiakos, Y.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
An improved calibration method for the non-destructive determination of the manganese content in large metallurgical tap smelting slag samples using photon activation analysis is presented. A metallurgical tap smelting slag of archaeological interest from the Psaphaki site, Laconia, was irradiated under the mixed photon and parasitic neutron field produced by an 18 MV medical accelerator. The sample was 236 g in mass. Manganese was determined by the photon and neutron induced reactions 55Mn(g, n)54Mn and 55Mn(n,g)56Mn, measuring the 834.8 keV 54Mn and 846.8 keV 56Mn photopeaks, respectively. Gamma spectra from the large sample and calibration foils were acquired using a HPGe detector of 85% relative efficiency. The Efficiency Transfer method was applied to determine the Full Energy Peak Efficiency (FEPE) of the large sample. The results of the analysis showed that the manganese content in the slag was (39.5±15.8) % w/w and (39.7±2.6) % w/w measuring the 56Mn photopeak and the 54Mn photopeak, respectively. Therefore, a good agreement between the photon and neutron activation analysis techniques was observed. Advantages of the technique include improved representativeness of results, elimination of reference samples, irradiation versatility and convenience, as well as reduced contamination probability since a minimal sample preparation was required for the analysis. Moreover, the introduction of the relative calibration technique removes the dependency on parameters that are usually evaluated with larger uncertainties, such as detector efficiency, increasing the quality and reliability of the procedure.